Pengaruh Dana Otonomi Khusus terhadap Fly paper effect di Provinsi Aceh - T Zulfan; Era Mustika (Jurnal EMT KITA, 2018)
The granting of authority in financial arrangements or tax decentralization is expected to stimulate the improvement of public sector services. Nevertheless, regions with no large funding revenues are accompanied by defects in Regional Original Income (PAD). The indication of inefficiency in the transfer fund can be seen from the method of financial data analysis. The flypaper analysis model is one of the methods of researching financial performance with regional government expenditure with regional revenue sources. The analysis technique uses Data Panel data regression in 23 districts/cities of Aceh Province in 2008-2017. Based on the credit results in 23 districts/cities in Aceh Province, it can be interpreted that the influence of the flying paper phenomenon is based on OTSUS. The partial test results indicate that variable PAD is in fact not significant to regional expenditure. So at this time, the tax source from PAD has not moved on the regional shopping list. Conversion results on the OTSUS variable on regional spending have a positive, significant direction, and are greater than the PAD on regional spending. The high character of OTSUS funds, including the symptoms of the flypaper effect, occurred in the financial sector in Aceh Province.